ANALISIS SEMIOTIK ROLAND BARTHES MODEL SIGNIFIKANSI DENOTASI DAN KONOTASI DALAM PUISI KARAWANG BEKASI KARYA CHAIRIL ANWAR DAN PEMANFAATANNYA SEBAGAI ALTERNATIF BAHAN AJAR SASTRA INDONESIA DI SMA - Meli Herawati; Rendy Triandy; Eggie Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the semiotics in the poetry collection Karawang Bekasi by Chairil Anwar. The focus of this study is the development of semiotic analysis in the poetry collection Karawang Bekasi by Chairil Anwar towards Indonesian language learning in high school. The method used in this study is a qualitative semiotic method with a denotation and connotation model. The data collection technique in this study is the reading and note-taking method or literature study. The data validation test in this study uses the triangulation technique. The data source of this study is the poetry book Karawang Bekasi by Chairil Anwar, the data obtained are in the form of denotation and connotation meanings that show a relationship with semiotic analysis. Based on the results of the study in the poetry of Karawang Bekasi by Chairil Anwar, data were found containing semiotics according to Roland Barthes' theory. The results of the semiotic analysis in the poetry collection Karawang Bekasi by Chairil Anwar can be used as an alternative teaching material for poetry texts in high school. In accordance with the results of the semiotic analysis of the Karawang Bekasi collection by Chairil Anwar, there are several aspects in the form of characteristics of poetry, types of poetry, and elements of poetry so that the Karawang Bekasi poetry collection by Chairil Anwar is related to Indonesian language learning in high school.